Gestational hypercholanemia suppresses pregnancy‐associated adipose mass increase and stimulates a pro‐inflammatory environment in mice - Vanya Nikolova; Alice L. Mitchell; Elena Bellafante; Eugene Jansen; Georgia Papacleovoulou; Per‐Olof Bergh; Hanns‐Ulrich Marshall; Catherine Williamson (Physiological Reports)
Abstract Women with intrahepatic cholestasis of pregnancy (ICP) have hypercholanemia alongside an increased risk of dyslipidemia. We investigated how cholic acid (CA) supplementation in murine pregnancy impacts adipose tissue function. Mice were fed normal or 0.5% CA‐supplemented chow from identification of copulatory plug until gestational day 14 or 15 (n = 10–11/group) and were matched experimentally with nonpregnant mice (n = 7/group). Tissue weights were measured alongside plasma bile acids, glucose, lipids, reactive oxygen metabolites (ROM), and adipokines. Subcutaneous and gonadal adipocyte mRNA expression was evaluated. CA supplementation inhibited pregnancy‐associated adipose tissue expansion and decreased fetal weight. CA diet in pregnancy increased LDL‐cholesterol and reduced HDL‐cholesterol. Pregnancy and CA diet reduced lipid metabolism transcript expression in adipocytes. CA supplementation during pregnancy increased plasma ROM by 1.24‐fold and suppressed inflammatory‐modulating pentraxin‐2/3 and insulin‐like growth factor 1 (IGF‐1) levels by >50% and >80%, respectively. Together, we show that hypercholanemia disturbs pregnancy‐associated adipose tissue expansion and mRNA expression in late gestation concomitant with reduced IGF‐1, altered lipid availability and increased inflammation and oxidation, which could impact fetal growth. This work highlights the need to better understand adipose tissue and redox stress changes in ICP pregnancies and the potential implications for fetal health.